“Indigenous” / “Afro” Theatre? Reconstructing Indigenous and Afrodescendent Lives on Stage Within and Beyond Art/Activism - Cañuqueo, Lorena (2021)
Fil: Cañuqueo, Lorena. Universidad Nacionald de Río Negro. Río Negro, Argentina.